A pattern of partially homologous recombination in mouse L cells. - Anderson, R A (1984)
Herpes simplex virus thymidine kinase gene and pBR322 DNA (in large excess to the thymidine kinase gene) were introduced into mouse L cells by calcium phosphate DNA-mediated gene transfer. DNA fragments encompassing six junctions between the exogenous DNAs have been cloned and their nucleotide sequences determined. Analysis of these sequences has shown that stretches of partial homology involving from 20-50 base pairs are present near the points at which joining occurs between the donor molecules. The structure of the junction sequences suggests that the recombination event involves the alignment of the two donor DNA molecules at partially homologous regions followed by staggered cutting and joining. One donor molecule is always cut in the region of partial homology, while the second is cut at some distance that is a small multiple of 13.5 +/- 0.5 base pairs away (at 0, 14, 27, 39, 41, and 54 base pairs). In the three junctions where the second cut is far from the region of homology, a 17- to 19-base-pair segment of DNA separates the donor sequences. In all cases the origin of this "filler" DNA appears to be oligonucleotides derived from pBR322.